HOW INTERPRETING BUSINESS PRINCIPLES THROUGH THE LENS OF “NEW SCIENCE” CAN HELP SOCIAL ORGANIZATIONS RESPOND TO GLOBAL AND LOCAL THREATS AND OPPORTUNITIES WHILE PROTECTING THEIR GOALS AND VALUES: A HEALTH CARE EXAMPLE OF SCIENTIFIC HUMANISM, COMPLEXITY, A - Paul Becker (European Scientific Journal, ESJ, 2014)
Canadian governments and their publically-funded health authorities are under increasing pressure to provide timely and quality services to a growing and aging population. They are also expected to use business principles and tools to make the health care system more efficient and to reduce costs through innovation and change. Business principles such as strategic planning, process re-engineering and improvement, balanced scorecards for performance measuring and reporting, and systems design and optimization are based on scientific concepts that can be traced back through Taylorism of the early 1900s to the Industrial Revolution to early discoveries in mathematics and physics. As well as employing science-based business practices in order to increase the efficiency of the health care system, health care leaders must also employ social values in order to be patient-centered. These social constructs are based on humanistic versus mechanistic principles. How, then, can the health care system achieve its social goals if the business principles it has come to rely on may actually be contrary to its patient-centered values? Viewing health care leadership and management through the lens of ―New Science‖ can help reconcile these seemingly contrary philosophies. ―New Science‖ takes scientific management concepts beyond Newton, Taylor, and Einstein and employs a systems and ecological view of life in health care organizations. ―New Science‖ goes beyond quantum mechanics and includes uncertainty and unpredictability, complementarity, semantic and chaotic infinite complexity, non-linear adaptive feedback networks, and wholeness and implicate order.